Higher education and SDG2 : zero hunger - Cripps, Karen; Thondre, Pariyarath Sangeetha (Higher education and the sustainable development goals, 2024)
In a post-COVID-19 pandemic era of cost-of-living crises and global displacements of people due to conflicts and climate challenges, food poverty is a growing and ever-pressing issue across both the Global North and the Global South. Presenting a collection of cases drawn from higher education research, teaching and learning, as well as campus and community-based initiatives, Higher Education and SDG2 addresses food security, nutrition, sustainable and resilient agriculture, and ending hunger for all. Featuring chapters and cases from Australia, Canada, China, Indonesia, Italy, Malawi, Northern Ireland, Peru, Turkey, the UK, the USA, Vietnam and Zimbabwe, this edited collection demonstrates the fundamental role Higher Education has in helping deliver Zero Hunger. The chapters cover education, research and community engagement initiatives that aim to address how this issue impacts the nations that face the most widespread and severe effects of hunger, food insecurity, malnutrition, and unsustainable food systems. Focusing on opportunities for Higher Education to positively influence academic, innovation, and policy agendas, this synthesis of global approaches is an inspirational call to action for increasing meaningful engagement by universities and colleges to address SDG2 Zero Hunger. Higher Education and the Sustainable Development Goals is a series of 17 books that address each of the SDGs through the lens of higher education. Adopting a solutions-based approach, each book focuses on how higher education is advancing delivery of Agenda 2030. The series is edited by Wendy Purcell, Professor with Rutgers University and Academic Research Scholar with Harvard University; Emeritus Professor and University President Emerita.